Impact of resistance exercise and nutritional endorsement on physical performance in patients with GvHD (IRENE-G study): design and rational of a randomized controlled trial - Bujan Rivera, Janina; Kühl, Rea; Zech, Ulrike; Hendricks, Anne; Luft, Thomas; Dreger, Peter; Friedmann-Bette, Birgit; Betz, Theresa Maria; Wiskemann, Joachim (BMC cancer, 2022)
Graft-versus-host disease (GvHD) remains a major complication and limitation to successful allogeneic hematopoietic stem cell transplantation. Treatment of GvHD is challenging due to its heterogeneous nature of presentation, with steroids remaining the established first-line treatment. Long-term doses of systemic corticosteroids have many well-known side-effects including muscle atrophy. Despite the fact that reports in non-cancer clinical populations treated with glucocorticoids demonstrated that resistance training can reverse atrophy and weakness, no RCT has evaluated the potential of resistance training on preventing the disease- and treatment-induced loss of skeletal muscle mass and function in GvHD patients yet. In this context, ensuring adequate nutrition is important as protein deprivation may accelerate the wasting process. As GvHD patients are commonly found to be malnourished, nutritional medical care should be considered when investigating the effect of exercise in GvHD patients. Therefore, the aim of the present “Impact of Resistance Exercise and Nutritional Endorsement on physical performance in patients with GvHD” - Study (IRENE-G) is to evaluate the effects of resistance exercise in combination with nutritional endorsement on physical, nutritional and patient-reported outcomes in GvHD patients. The study will contribute to our understanding of the value of exercise and nutritional endorsement in counteracting the negative consequences of GvHD and its treatment.
Gesehen am 01.06.2022